PENGARUH VARIASI UKURAN V-BELT DAN SUDUT ALUR PADA PERMUKAAN KAMPAS KOPLING CVT TERHADAP DAYA DAN TORSI SEPEDA MOTOR 125 CC: THE EFFECT OF V-BELT SIZE AND GROOVE ANGLE VARIATION ON THE SURFACE OF THE CVT CLUTCH DISK ON THE POWER AND TORQUE TRANSMISSION OF 125CC MOTORCYCLE - Adi Putra, Rengga (Jurnal Teknik Mesin, 2023)
Continuously Variable Transmission (CVT) is an automatic transmission system with gear ratio shifts following engine speed controlled by the primary and secondary pulleys, as well as the V-belt that connects the two pulleys. The disadvantage of the CVT transmission system is that it often loses grip on the CVT clutch lining and the V-belt at low and high rotation so that research needs to be done so that the power from the engine to the wheels can be maximized. This study used an experimental method by changing the variation in the size of the V-belt and the groove angle on the clutch pads to find the best size for a 125 CC motorbike. The results showed that to get maximum results it is recommended to use a V-belt 803 x 19.0 mm with a CVT lining of 30° producing the highest power and a V-belt 840 x 21.8 mm with a CVT lining of 90° producing the highest torque